The influence of corruption and governance in the delivery of frontline health care services in the public sector: A scoping review of current and future prospects in low and middle-income countries of south and south-east Asia - Naher, Nahitun; Hoque, Roksana; Hassan, Muhammad Shaikh; Balabanova, Dina; Adams, Alayne M.; Ahmed, Syed Masud (BMC, 2022)
This article was published in BMC Public Health [ © The Author(s). 2020 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License] and the definite version is available at: https://doi.org/10.1186/s12889-020-08975-0 The Journal's website is at: https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-020-08975-0#citeas